(3MGTjI GdMajO Ydi TQM GdJdNjU GdeNJUQ ddJaJGRGfjs - (3GdMajO (B= (3MajO GdSYO, CMeO Hf jMji Hf eMeO, J(B916(3g`s ((3eMeO Hf jMji Hf OGhOs)
(3ChdgG (B:s
(3bhdg(B: (3fMeOc EfeG GNJGQ GdMeO Ydi GdTcQ eY Cf GdeJHGOQ ef GdYHGQI Cf GdeMehO Ydjg gfG fYeI GfTQGM GdUOQs
(3BNQgG (B:s
(3bhdg(B: (3aef RYe Cfg cGf jfHZjCfJ NHjQ HCf GdeYfi GdPj PcQg GdTGQM bOS SQg ZjQ XGgQ ef GdYHGQI JCed hGddg CYde HGdUhGHs
(3fSNI efbhdI Yf fSNI GdeDda (B889(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 1 / 270s
(3eYLe GdeDdajf(B: 1 / 325s
(3cTa GdXfhf(B: 1 / 475s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdHdGZIs